Characterization of the human intervertebral disc cartilage endplate at the molecular, cell, and tissue levels. Issue 9 (24th September 2020) - Lakstins, Katherine; Arnold, Lauren; Gunsch, Gilian; Flanigan, David; Khan, Safdar; Gadde, Nikhit; Jones, Blain; Agarwal, Gunjan; Purmessur, Devina
Abstract: Given the importance of the cartilage endplate (CEP) in low back pain (LBP), there is a need to characterize the human CEP at the molecular, cell, and tissue levels to inform treatment strategies that target it. The goal of this study was to characterize the structure, matrix composition, and cell phenotype of the human CEP compared with adjacent tissues within the intervertebral joint: the nucleus pulposus (NP), annulus fibrosus (AF), and articular cartilage (AC). Isolated CEP, NP, AF, and AC tissues and cells were evaluated for cell morphology, matrix composition, collagen structure, glycosaminoglycan content, and gene and protein expression. The CEP contained elongated cells that mainly produce a collagen‐rich interterritorial matrix and a proteoglycan‐rich territorial matrix. The CEP contained significantly fewer glycosaminoglycans than the NP tissue. Significant differences in matrix and cell marker gene expression were observed between CEP and NP or AF, with the greatest differences between CEP and AC. We were able to distinguish NP from CEP cells using collagen‐10 (COLX), highlighting COLX as a potential CEP marker. Our findings suggest that at the cell and tissue levels, the CEP demonstrates both similarities and differences when compared with NP, AF, and hyaline AC. This study highlights a unique structure, matrix composition, and cell phenotype for the human CEP and can help to inform regenerative strategies that target the intervertebral disc joint in chronic LBP.